METHODS OF SETTING AND SOLVING MIXED AND BOUNDARY PROBLEMS FOR HYPERBOLIC TYPE EQUATIONS - Elvira Erkin kizi Shakayeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the methods of solving these mixed and boundary problems are described. The Sturum-Liouville problem is described and the solution of such problems by the Fourier method is shown. The mixed problem put into the hyperbolic type equation was solved by the Fourier method.